Enhancing environmental literacy and argumentation skills: Developing a PjBL-based interactive e-module integrating local ecological issues - Yasma; Suwono , Hadi; Rahayu , Sofia Ery (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2026)
Small islands face environmental threats from human activities and climate change, highlighting the need for contextual learning to empower students’ environmental literacy and argumentation skills in addressing these issues. This study aimed to develop a PjBL-based interactive e-module integrating local ecological issues from Sanrobengi Island to enhance high school students’ environmental literacy and argumentation skills. This study employed a Research and Development (R&D) design based on Plomp and Nieveen model, consisting of preliminary research, development or prototyping, and assessment phases. The effectiveness of the developed e-module was evaluated using a quasi-experimental pre-test-post-test non-equivalent control group design. The assessment phase involved tenth-grade students from SMA Negeri 5 Takalar, Indonesia, consisting of an experimental class (N = 30) and a control class (N = 27). Expert validation indicated that the e-module was highly valid and practical (>95%). Effectiveness testing revealed moderate improvements (N-Gain = 0.5) in the EL cognitive domains as well as in the argumentation skills. Conversely, the affective and behavioral dimensions of EL exhibited lower improvement (N-Gain = 0.3). Furthermore, ANCOVA results confirmed that the e-module significantly enhanced students’ cognitive EL and argumentation skills (p < 0.001), while its impact on the affective (p = 0.165) and behavior (p = 0.111) dimensions were not statistically significant. These findings suggested that the e-module effectively strengthened students’ cognitive foundation and argumentation skills. However, the relatively short intervention period and limited direct environmental engagement may have constrained improvements in students’ environmental attitudes and behaviors.